Spin-orbit coupling induced splitting of Yu-Shiba-Rusinov states in antiferromagnetic dimers - Philip Beck (Nature Portfolio, 2021)
The influence of spin-orbit coupling on the hybridization of Shiba states in dimers of magnetic atoms on superconducting surfaces remains unexplored. Here, the authors reveal a splitting of atomic Shiba orbitals due to spin-orbit coupling and broken inversion symmetry in antiferromagnetically coupled Mn dimers placed on a Nb(110) surface.